Role of color doppler ultrasonography in high risk pregnancies: a retrospective study - Kavitha, Gayak; Palakodeti, Nirupama; Samalla, Silpahasa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Numerous adverse perinatal outcomes are associated with high-risk. The usage of doppler ultrasound bids a non-invasive way to study the fetal and maternal circulation and guide the clinical management. Objective of this study was to investigate the role of color doppler ultrasonography in effective management of high-risk pregnancies. Methods: A retrospective record-based study was carried out Department of obstetrics and gynecology. Record of antenatal women who belonged to the age group of 20-30 years with singleton pregnancy of gestational age of 26 weeks to term and presence of one of the high-risk factors were included in the study. The risk factors which were considered are pregnancy-induced hypertension (PIH), diabetes, anemia, oligohydramnios. Doppler study of umbilical artery was done. Epi-info 7 was used for analysis. Results: A total of 140 cases were studied in which high-risk pregnancy was most common in the age group of 20-25 years. The most common high-risk factor in pregnancy was PIH which accounted for 50% of cases. Out of 140 cases high-risk pregnancies, 40% of cases resulted in intrauterine growth restriction (IUGR). 43% of cases, umbilical artery findings were abnormal. Conclusions: Color doppler can be used as most effective for fetal surveillance in high-risk pregnancy cases. Most importantly it helps in guiding early intervention and improving fetal outcome.